Sistem Informasi Penjualan Coklat dan Aneka Kue Berbasis Web Pada Toko Coklat Kiloan, Tambun Selatan - Ismail, Arie Agung; Faizah, Siti (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2024)
Abstract— The buying and selling process system at Kiloan Chocolate Shop still uses a manual method,namely by having buyers come to the Kiloan Chocolate Shop or order via telephone directly from the buyer'smobile phone to the admin's mobile phone, which is less effective. By observing and collecting the data andinformation needed, the author conducts an analysis, and the results of the analysis are implemented intoa program. With this program, the author hopes that the facilities and services provided to buyers will beoptimal. Likewise with the reports that ran before, where the form of sales reports was still made manuallyby handwriting on scraps of paper, and that form would be reported to the owner, as well as stock reportsthat still use Excel in each stock report. With this Kilo Chocolate Shop website, it is hoped that it can helpthe transaction process and the form of reports whose processes will be recorded into the system. Thisprogram can also help relieve store staff because all forms of transactions and reports are recorded in thesystem. For buyers, it is also very easy to shop and to be informed of the status of products that have beenpurchased.